Beyond Romer and Lawrence: The Right to Privacy Comes Out of the Closet - Marcus, Nancy C. (Columbia Journal of Gender and Law, 2006)
On Independence Day weekend, 2005, Justice Sandra Day O’Connor took much of the legal world by surprise by announcing her retirement from the Supreme Court. Two months later, Chief Justice Rehnquist’s death left another vacancy on the Supreme Court. O’Connor’s presumed replacement, John Roberts, was immediately named as Rehnquist’s replacement and the new Chief Justice of the United States Supreme Court. With the dramatic changes on its bench, the Supreme Court is at a historic crossroads, warranting a retrospective examination of the paths the Court has taken previous to and during the Rehnquist Court era, and the bridges it may cross in the time to come. In particular, this Article examines the significant developments in the Court’s privacy rights jurisprudence with a look ahead toward the future of privacy rights and liberty interests under a new Supreme Court. As the Rehnquist era comes to a close, it promises to leave a legacy which includes surprisingly strong protections for liberty and equality. The Rehnquist Court has issued a series of forceful opinions affirming substantial Fourteenth Amendment protections for individual autonomy in recent years, culminating with the gay rights decisions Romer v. Evans4 and Lawrence v. Texas.